I can do that! 1000 ways to become independent - Bryant, Ray; Hifumiyo; Laboile, Alain (London dorling kindersley, 2023)
"In I Can Do That, photos and illustrations combine to produce a value-packed resource for families preparing for their child's big life stages. Young readers can learn how to lace up their shoes, put on a sweater, go to the toilet, peel fruit, count to 100, and brush their teeth. Step by step instructions sit alongside more than 700 fun and helpful photos and illustrations to help children practice and learn. The short and practical text will help your child learn to be independent. As they grow up, they will be able to say, "I can do that!" every time they turn the page. Perfect for families following Montessori practices and caregivers keen for their children to develop natural interests at their own pace, I Can Do That is an extraordinary book that both parents and kids will love!
Education
Keywords: Children Health and hygiene; Life skills -- Juvenile literature; Personal grooming -- Juvenile literature